Dampak Penggunaan Paylater Terhadap Minat dan Gaya Hidup Karyawan PT Tripatra - Dhea Paramitha (Transformasi: Journal of Economics and Business Management, 2025)
PayLater services are increasingly popular as a payment method that offers ease of transactions and financial flexibility for its users. However, this convenience can also increase consumptive behavior that has the potential to affect individual financial stability. This study aims to analyze the impact of PayLater service on consumption interest and lifestyle of PT Tripatra employees. This research uses a quantitative approach with a survey method. Data was collected through questionnaires distributed to PT Tripatra employees who use PayLater services. Data analysis was performed with descriptive statistical tests and linear regression to measure the relationship between PayLater usage, consumption behavior, and financial stability. The results showed that the PayLater service provided significant benefits in the ease of transactions and increased employee purchasing power. However, there is a positive correlation between the use of this service and an increase in consumptive behavior, including impulse purchases. This has the potential to reduce individual financial stability in the long run, especially for those who lack good financial literacy. Uncontrolled use of PayLater services can increase financial risk. Therefore, awareness and good financial literacy are needed so that the benefits of this service can be optimized without causing negative impacts. As a recommendation, companies are advised to provide financial education to their customers.